Trans-osseous intraoperative limb length measurement in hip replacement surgery - Pilar, Anoop; Rao, Srivatsa Nagaraj; Muniswamy, Madan Mohan; Manohar, Sandesh G; Amaravathi, Rajkumar S. (International Journal of Research in Orthopaedics, 2020)
Background: Discrepancy of the limb length following total hip replacement is one of common complication. To reduce the occurrence, various modalities are used like pre-operative templating, navigation assisted measurements and intraoperative methods. This study was done using trans-osseous method of measurement using hip gauge which provides a faster, simpler assessment of limb length. Methods: A prospective study of 25 patients who underwent uncemented hip arthroplasty was taken in the study and the LLD was measured before and after the surgical procedure. Patient were re-assessed for limb length discrepancy after 6 months with functional Harris hip score and radiological analysis on weight bearing standard X-ray antero-posterior view of the pelvis with bilateral hip joint. Results: The results showed significant improvement in limb length discrepancy, and analysis of postoperative radiographs found the mean length difference of 2.44 mm and average Harris hip score was 95.5. No device related complications were reported, and none of them complained of the discomfort related to limb-length discrepancy after surgery. Conclusions: Trans-osseous fixed method using hip gauge provides a faster, reproducible and simpler method for the assessment of Limb length and aids with offset placement, acetabular anteversion for precise cup placement. This is a reliable method as it can be used both in the primary and revision hip surgery and most importantly doesn’t require any additional intraoperative imaging.